Diagnostic Evaluation of Visual Snow - Vaphiades, Michael S.; Grondines, Brendan; Cooper, Kasey; Gratton, Sean; Doyle, Jennifer (Frontiers in Neurology, 2021)
Introduction: to determine which patients with visual snow (VS) and visual snow syndrome (VSS) require standard ophthalmologic testing including automated visual field, and which patients require further testing such as macular spectral domain optical coherence tomography (SD-OCT), electrophysiology and neuroimaging. Materials and Methods: We retrospectively reviewed 52 consecutive patients at 3 institutions with VS and VSS including the University of Alabama, Callahan Eye Hospital, University of Missouri-Kansas City School of Medicine and the Little Rock Eye Clinic from the years 2015 to 2021. We collected historical information, examination findings, ophthalmic testing, electrophysiology, and neuroimaging. Results: Of the 52 patients with VS and VSS, 8 of the 52 cases met the clinical criteria for VSS. The ages ranged from 7 to 79 years, with a mean age of 25 years (SD = 14.0). There were 22 males and 30 females. Color vision was tested in 51 cases and was normal in 47 cases (92%). A funduscopic exam was performed in all 52 cases and was normal in 46 cases (88%). The macular SD-OCT was normal in all of the 19 cases that it was performed (100%). A Humphrey visual field was performed in 50 cases and was normal in 43 (86%). A VEP was normal in 18 of the 19 cases where it was obtained (95%). The ffERG was obtained in 28 cases and was normal in 25 (89%). The mfERG, was normal in 11 of 12 cases (92%). Only 4 patients accounted for all of the abnormal electrophysiologic tests. In the 37 cases that had an MRI, 29 were normal (78%). Only one patient revealed a lesion in the visual pathway (right optic nerve enhancement in an optic neuritis patient). Conclusions: Patients with VS and VSS, if typical in presentation and with normal testing, do not require a work-up beyond a thorough history, neuro-ophthalmological examination and automated perimetry. If this testing is abnormal however, then ancillary testing is required.